2018
DOI: 10.3390/jmse6020039
|View full text |Cite
|
Sign up to set email alerts
|

Deployment and Maintenance of Wave Energy Converters at the Lysekil Research Site: A Comparative Study on the Use of Divers and Remotely-Operated Vehicles

Abstract: Ocean renewable technologies have been rapidly developing over the past years. However, current high installation, operation, maintenance, and decommissioning costs are hindering these offshore technologies to reach a commercialization stage. In this paper we focus on the use of divers and remotely-operated vehicles during the installation and monitoring phase of wave energy converters. Methods and results are based on the wave energy converter system developed by Uppsala University, and our experience in offs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…A choice of threshold of 3 m or higher for the significant wave height should be recognized as a fairly high threshold, and crews and divers would likely avoid operating above 1.5 m to 2 m, even if the marine vessel used was capable of operating in those conditions. However, it may be possible that more of the required O&M for near-shore and offshore energy devices would be performed using Remotely Operated Vehicle (ROV) robotics and Autonomous Underwater Vehicles (AUVs) in the future [45,63,64], so that higher threshold values could be useful to consider. Based on experiences from the Lysekil research site on the west coast of Sweden, a comparative study on the use of divers and ROVs found economic advantages for ROVs starting from seven deployed devices or more [45].…”
Section: Assessment Of Operations and Maintenance Conditions Using Timentioning
confidence: 99%
See 1 more Smart Citation
“…A choice of threshold of 3 m or higher for the significant wave height should be recognized as a fairly high threshold, and crews and divers would likely avoid operating above 1.5 m to 2 m, even if the marine vessel used was capable of operating in those conditions. However, it may be possible that more of the required O&M for near-shore and offshore energy devices would be performed using Remotely Operated Vehicle (ROV) robotics and Autonomous Underwater Vehicles (AUVs) in the future [45,63,64], so that higher threshold values could be useful to consider. Based on experiences from the Lysekil research site on the west coast of Sweden, a comparative study on the use of divers and ROVs found economic advantages for ROVs starting from seven deployed devices or more [45].…”
Section: Assessment Of Operations and Maintenance Conditions Using Timentioning
confidence: 99%
“…The seasonal ice-cover of the Baltic Sea [39,40] is, however, known to influence the wave climate, and Tuomi et al [41] suggested ways to calculate different types of statistics taking the ice-time into account. In practice, experience from both the WESA (Wave Energy for a Sustainable Archipelago) project [42][43][44] and several field tested deployment strategies [45,46] of wave energy equipment have increased the awareness of wave energy as an available potential renewable energy source in the region. Wave energy converters are, however, not very likely to be deployed if the presence of sea-ice is consistent for long periods of time every year.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations by Yang et al (2017) showed that biofouling on mooring lines and power cables associated with wave energy converters reduced energy performance (up to 17%) and caused significant reductions (up to 76%) in the fatigue life of moorings. Wave energy converters have been designed for 20-25 years of maintenance-free service, however, supporting infrastructure such as safety lines, underwater cables, and subtidal equipment may be prone to biofouling (Rémouit et al, 2018). As an emerging technology, there is little information on biofouling management approaches for wave energy converters, although manual or mechanical cleaning via diving and ROVs may be required (Rémouit et al, 2018) and should be considered in economic forecasting.…”
Section: Energy Productionmentioning
confidence: 99%
“…2 km off the Swedish west coast near the Islandsberg lighthouse. The site is marked at the northern and southern boundaries with a sea marking (northern marking 58 • 11 850 N; 11 • 22 460 E and southern marking 58 • 11 630 N; 11 • 22 460 E) (Figure 1A) and covers an area of around 0.5 km 2 [49]. The seafloor at the research site is at a depth of 25 m, consists of sand, and shows little relief [50].…”
Section: Study Areamentioning
confidence: 99%